Cutaneous Expression of Familial Cancer Syndromes - Anne-Johanne Andersen; Juliane Schierbeck; Anette Bygum; Nieves Puente-Pablo (Medical Journals Sweden, 2021)
Genodermatoses are inherited syndromes with cutaneous manifestations. Some genodermatoses are associated with malignancy of internal organs and tissues. Early detection of the typical signs of these syndromes is important, because those lesions are a sign of underlying predisposition to extracutaneous neoplasms. The dermatologist has an important role in the early detection of these signs and syndromes, as early detection may affect the clinical course of the disease. We report here the characteristic cutaneous findings that dermatologists should be aware of in order to identify a genodermatosis with a possible associated malignancy. An updated overview of the pathogenesis and clinical findings of these syndromes is provided. Furthermore, surveillance protocols and treatment recommendations are explored.